91.4k views
20 votes
Help me...

solve.
5×4^(x+1)-6^x=64​

User Cnk
by
6.5k points

2 Answers

10 votes

Step-by-step explanation:

5×4^(x+1)-16^x=64

0=64+16^x-5×4¹×4^x

0=(4^x)²-2×4^x×10+10²-10²+64

0=(4^x-10)²-36

(4^x-10)²=36

4^x-10=√36

4^x=+-6+10

when positive

4^x=4²

:.x=2

when negative

4^x=4

:.x=1

User Artem Kalachev
by
5.4k points
3 votes

Answer:

5×4^(x+1)-6^x=64

Graph each side of the equation. The solution is the x-value of the point of intersection.

x≈0.8927896,7.38810359

image of graph

Step-by-step explanation:

Hope it is helpful....

Help me... solve. 5×4^(x+1)-6^x=64​-example-1
User Jamz
by
5.3k points